2022
DOI: 10.3389/fgene.2021.753624
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Analysis of the Ascorbate Peroxidase (APX) Gene Family of Winter Rapeseed (Brassica rapa L.) Under Abiotic Stress

Abstract: Winter Brassica rapa (B. rapa) is an important oilseed crop in northern China, but the mechanism of its cold resistance remains unclear. Ascorbate peroxidase (APX) plays important roles in the response of this plant to abiotic stress and in scavenging free radicals. In this study, the roles of APX proteins in the cold response and superoxide metabolism pathways in rapeseed species were investigated, and a comprehensive analysis of phylogeny, chromosome distribution, motif identification, sequence structure, ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Genome-wide studies of various gene families in Brassicaceae have consistently indicated their expansion compared with Arabidopsis. Notable examples are not limited to but include APX, NPR, DOF, shattering genes, SOD, and PEBP [68][69][70][71][72][73]. Regarding amphidiploids, the presence of twelve genes suggests these species inherited six genes from each of their parental species, corresponding to the GTR genes found in Arabidopsis [42].…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide studies of various gene families in Brassicaceae have consistently indicated their expansion compared with Arabidopsis. Notable examples are not limited to but include APX, NPR, DOF, shattering genes, SOD, and PEBP [68][69][70][71][72][73]. Regarding amphidiploids, the presence of twelve genes suggests these species inherited six genes from each of their parental species, corresponding to the GTR genes found in Arabidopsis [42].…”
Section: Discussionmentioning
confidence: 99%
“…The positive clones were selected to interact with LR Clonase enzyme (Invitrogen, Carlsbad, CA, USA) to connect to the overexpression vector pEarly-Gate101, following the instructions for Agrobacterium tumefaciens GV3101 (Anyu Biotechnology Co., Ltd., Shanghai, China). After the bacteria were picked out from the coated plate, colony PCR was carried out, and the positive bacterial solution was selected and preserved [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…To date, the APX gene has been identified in many plants. Examples include pepper ( Capsicum annuum L.) ( Pang et al, 2023 ), tomato ( Solanum lycopersicum L.) ( Hu et al, 2021 ), upland cotton ( Gossypium hirsutum L.), winter rapeseed ( Brassica rapa L.) ( Ma et al, 2022 ), Arabidopsis thaliana ( Kameoka et al, 2021 ), and sorghum ( Sorghum bicolor L.) ( Akbudak et al, 2018 ). Additionally, various APX members have been recognized for their roles in abiotic stress responses.…”
Section: Introductionmentioning
confidence: 99%